The Influence of Social Media Marketing on Brand Equity and Brand Loyalty in Digital Banks: A Brand Trust Perspective - Vina Sandriana Ulfa; Abdul Haeba Ramli (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Social media is making marketing more effective for companies. The study examines how social media marketing affects digital bank brand equity and loyalty through brand trust. Explanatory quantitative research was used with 384 Greater Jakarta digital bank users. This study reveals that social media marketing boosts brand trust, equity, and loyalty. It has been shown that brand trust increases brand equity but not brand loyalty. Brand equity positively and significantly affected brand loyalty. This study found that interactive, relevant, amusing, and instructive social media marketing can boost brand equity by increasing consumer trust. Companies must also consider customer experience and satisfaction to directly increase brand loyalty. These insights help digital bank management create effective social media marketing strategies to develop brand trust, equity, and loyalty. Further research with larger geographic coverage and more variables can provide more thorough insights